Využití Business Intelligence pro hledání závislostí v dotazníkových šetřeních - Janata, Michal (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Tato diplomová práce se zabývá vytvořením aplikace pro analýzu dotazníků. V první části jsou uvedeny teoretické základy z přímého marketingu a Business Intelligence. Další kapitola je zaměřena na dostupné nástroje pro analýzu dat a BI. V této části je také zahrnuta analýza a příprava vstupních dat. Na závěr je předložen vlastní návrh řešení.

This master’s thesis is focused on creating an application for survey analysis. In the first section are theoretical foundations of a direct marketing and Business Intelligence. The next chapter focuses on available tools for data analysis and BI. Analysis and preparation of input data are also included in this part. Finally, the solution proposal is presented.
Searching for Dependencies in the Questionnaire Surveys Using Business Intelligence
Keywords: Business Intelligence; Data Mining; přímý marketing; integrační služby; analytické služby; SQL server.; Business Intelligence; Data Mining; Direct Marketing; Integration Services; Analysis Services; SQL server.